(untitled) (Zien Journal of Social Sciences and Humanities, 2025)
Proverbs carry an indelible trace of the national character, wisdom, and spirit of a nation therefore, in every proverb we can see the image of folk who created these proverbs. In the article through proverbs, features of Uzbek national character which appeared on the basis of immortal and tenacious Uzbek values are defined and elucidated. According to the author, such traits as generosity, mercifulness, hospitality pertain to the nature of Uzbek ethnic group. Apart from this, the author discusses reasons for the formation such kind of formidable personality traits in Uzbek